Beating Burnout at Work Why Teams Hold the Secret to Well-Being and Resilience - Paula Davis (Philadelphia Wharton School Press, 2021)
Burnout has become one of the most talked about workplace topics, and its impact is far-reaching. The 24/7 pace of work, constant demands, and scant resources can easily put busy professionals on a path to burnout, a cycle that has only accelerated during the COVID-19 pandemic. Burnout affects the health and well-being of the entire organization, yet most attempts to help focus on quick-fix strategies aimed at individuals. Something is missing.
Includes Index
Keywords: Leadership